Explaining math and science achievement of public school children in the Philippines - Quimbo, Stella Luz A. (The Philippine Review of Economics, 2003)
This paper presents estimates of an education production function which includes measures of the home learning environment and school inputs recorded at the student level. These are important variables but are often overlooked as a result of data limitations. Results suggest that minimizing teacher absenteeism and effectively providing basic learning materials in schools can improve the math and science achievement of current as well as future generations of students. The home learning environment, including parental education, was found to have a significant effect on student performance.